2020
DOI: 10.54112/bcsrj.v2020i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antibacterial Activity of Aloe Vera Plant Extract

Abstract: Aloe vera is a well-known medicinal plant used in many therapeutic purposes. Naturally it is composed of many useful compounds that have ability to use for treatment of many diseases. The active compounds reported in this plant are saponins, sugar, enzymes, vitamins, aloesin, aloeemodin, aloin, acemannan aloemannan, aloeride, methylchromones, flavonoids, naftoquinones, sterols, minerals, anthraquinones, amino acids, lignin and salicylic acid and other different compounds including fat-soluble and water-soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 23 publications
1
44
1
Order By: Relevance
“…Finally, the anthraquinones and derivates of A. vera root have antiviral action reported against influenza AH1N1 virus (Borgesarg aez et al, Dammak et al, 2018). (Etusim et al, 2013) found that A. vera root extracts also have antibacterial biological activities, mainly against Pseudomonas aeruginosa, Salmonella typhi and Proteus mirabilis Danish et al (2020). found that A. vera root extracts also have antifungal activity against Userium oxysporum, Candida albicans, Aspergillus fumigatus, and Aspergillus niger.…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…Finally, the anthraquinones and derivates of A. vera root have antiviral action reported against influenza AH1N1 virus (Borgesarg aez et al, Dammak et al, 2018). (Etusim et al, 2013) found that A. vera root extracts also have antibacterial biological activities, mainly against Pseudomonas aeruginosa, Salmonella typhi and Proteus mirabilis Danish et al (2020). found that A. vera root extracts also have antifungal activity against Userium oxysporum, Candida albicans, Aspergillus fumigatus, and Aspergillus niger.…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…It has been used as a folk medicine in many countries as anti-bacterial, anti-fungal, anti-inflammatory, anti-microbial, anti-oxidant, anti-viral, astringent and preservative. It has also been used for cancer prevention, cellular regeneration, lowering of cholesterol, cleansing, detoxification, heart health maintenance, lupus nephritis, rheumatoid arthritis and weight loss (Okunowo et al, 2013;Danish et al, 2020).…”
Section: Molisch's Testmentioning
confidence: 99%
“…Bacillus cereus, Bacillus megaterium, Bacillus subtitis, Streptococcus pyogenes, Staphylococcus aureus, E. coli, Pseudomonas aeruginosa, Acinetobacter baumannii, and other bacterial strains were employed in the study concluding that the use of plants in traditional medicine to treat a variety of ailments caused by these pathogenic strains is effective. 13 In an in vitro analysis, major active components of cinnamon stick such as (E)-cinnamaldehyde and proanthocyanidins exhibited important antibacterial potential against five foods containing bacteria, including Bacillus cereus, Listeria monocytogenes, Staphylococcus aureus, Escherichia coli, Salmonella anatum. 14 In another study by 13 common flavonoids i.e.…”
Section: Anti-oxidant Assaymentioning
confidence: 99%